Cognitive-behavioral therapy with couples and families a comprehensive guide for clinicians - Dattilio, Frank M. (Guilford Press, 2014)
From a leading expert in cognitive-behavioral therapy and couple and family therapy, this comprehensive guide combines research and clinical wisdom. The author shows how therapeutic techniques originally designed for individuals have been successfully adapted for couples and families struggling with a wide range of relationship problems and stressful life transitions. Vivid clinical examples illustrate the process of conducting thorough assessments, implementing carefully planned cognitive and behavioral interventions, and overcoming roadblocks. Used as a practitioner resource and text worldwide, the book highlights ways to enhance treatment by drawing on current knowledge about relationship dynamics, attachment, and neurobiology. Cultural diversity issues are woven throughout. See also Dattilio's edited volume, "Case Studies in Couple and Family Therapy," which features case presentations from distinguished practitioners plus commentary from Dattilio on how to integrate systemic and cognitive perspectives. -- Provided by publisher.